Frequency of Hearing Impairment in School-Going Children of District Hyderabad, Sindh, Pakistan: Frequency of Hearing Impairment - Bhatti, Muhammad Ali; Shaikh, Shakil Ahmed; Memon, Salma Farukh; Aamir, Kiran; Ramzan, Aamir; Shah, Hanozia (Pakistan Journal of Health Sciences, 2024)
Hearing impairment is prevalent disability in the general population; early intervention facilitates proper development. Without hearing rehabilitation, hearing impairment can cause detrimental effects on speech, language, developmental, educational and cognitive outcomes in children. Objective: This study aimed to document the frequency of hearing impairment in school-aged children of District Hyderabad, Sindh, Pakistan. Methods: This cross-sectional study was carried out in school-going children to find out the frequency of hearing loss of district Hyderabad, Sindh, Pakistan. The study was conducted from July 2023 to December 2023. The hearing threshold was assessed by a Type 2 audiometer (Manufactured by, Interacoustics A/S, Denmark). Hearing impairment was defined as ≥ 20 dB Hearing level. The results of hearing levels were independently documented in left and right ears, better and worse ears. The data obtained were analyzed on SPSS version 26.0. Statistical significance was set at P<0.05. Results: In this study, 1520 school-aged children were recruited. The mean age was 9.56 ± 1.56 years and most of the children were between 8 to 12 (85.7%) years. The frequency of hearing impairment was found 1.97%, and no age difference was found among participants. A positive relationship of neonatal icterus, and otitis media was found in participants. Conclusions: In this study, hearing loss was found in 1.97% of the population. It is suggested that the screening of children for hearing impairment is compulsory for diagnosis and treatment.